Utilização da técnica de DNA Barcode para a identificação de espécies de peixes de água doce comercializados nas regiões de Belo Horizonte e Muriaé - Glauber Batista Gois (2016)
Anthropogenic impacts are a rising threat to the diversity of fish, especially in areas around urban centers, and many effective conservation actions depend on accurate identification of species. Considering the usefulness of DNA Barcode as a global system of identification and discovery of species, this study aims to molecularly characterize the species of ornamental fish and provide partial COI gene sequences in a reference library. Following this methodology, a fragment of the subunit I of cytochrome oxidase gene was amplified and sequenced bidirectionally from 298. A Neighbor-Joining analysis showed that this approach can clearly discriminate all the surveyed species. Most of the species showed low intraspecific genetic distances (1.53%), about 9-fold less than the distance between species within a genus. The library developed in this study is a first step to better understand the molecular diversity of ornamental fish, providing a basis for future studies on this fauna - extending the ability to identify them in all life stages and even remnants or fragments, providing data for a better understanding of the interactions between species, generating estimates of the species composition and richness in an ecosystem, providing bioproducts authentication tools and monitoring illegal exploitation of species.